Cutaneous involvement in relapsed multiple myeloma. Issue 9 (5th September 2022) - Salle, Valéry; Attencourt, Christophe; Chevalier, Marion; Semeria, Lucile; Boulu, Xavier; Karam, Jean‐Denis; Smail, Amar; Schmidt, Jean; Duhaut, Pierre; Dernoncourt, Amandine
Abstract: Cutaneous involvement in multiple myeloma with extramedullary disease is rare. We report the case of a refractory multiple myeloma patient who developed a cutaneous lesion. Histopathology revealed dermal immature plasma cell infiltrate with a lack of CD138 expression. This cutaneous location was associated with an aggressive clinical course and short survival. Abstract : Cutaneous infiltration is a rare manifestation of multiple myeloma. It generally occurs at a late stage of the disease and is an ominous clinical sign. Skin involvement is usually associated with poor prognosis and requires aggressive therapies.